Outcomes of Direct Vision Internal Urethrotomy for Bulbar Urethral Strictures: Technique Modification with High Dose Triamcinolone Injection. (21st October 2015) - Modh, Rishi; Cai, Peter Y.; Sheffield, Alyssa; Yeung, Lawrence L.
Abstract : Objective . To evaluate the recurrence rate of bulbar urethral strictures managed with cold knife direct vision internal urethrotomy and high dose corticosteroid injection. Methods . 28 patients with bulbar urethral strictures underwent direct vision internal urethrotomy with high dose triamcinolone injection into the periurethral tissue and were followed up for recurrence. Results . Our cohort had a mean age of 60 years and average stricture length of 1.85 cm, and 71% underwent multiple previous urethral stricture procedures with an average of 5.7 procedures each. Our technique modification of high dose corticosteroid injection had a recurrence rate of 29% at a mean follow-up of 20 months with a low rate of urinary tract infections. In patients who failed treatment, mean time to stricture recurrence was 7 months. Patients who were successfully treated had significantly better International Prostate Symptom Scores at 6, 9, and 12 months. There was no significant difference in maximum flow velocity on Uroflowmetry at last follow-up but there was significant difference in length of follow-up (p = 0.02 ). Conclusions . High dose corticosteroid injection at the time of direct vision internal urethrotomy is a safe and effective procedure to delay anatomical and symptomatic recurrence of bulbar urethral strictures, particularly in those who are poor candidates for urethroplasty.